Chemical Constituents of Hoya cagayanensis C. M. Burton - Consolacion Y. Ragasa & , Melissa S. Borlagdan & , Fernando B. Aurigue, Robert BrkljaÄa, Sylvia Urban (Journal of Applied Pharmaceutical Science, 2017)
Chemical investigation of the dichloromethane extracts of Hoya cagayanensis led to the isolation of dihydrocanaric acid (1), lupeol (2), lupenone (3) and saturated hydrocarbons from the stems; and 2-hydroxyethyl benzoate (4) and a mixture of β-sitosterol (5a) and stigmasterol (5b) from the leaves. The structures of 1 and 4 were elucidated by extensive 1D and 2D NMR spectroscopy. The structures of 2, 3, 5a and 5b were identified by comparison of their NMR data with literature data.
Keywords: Apocynaceae, dihydrocanaric acid, Hoya cagayanensis C. M. Burton, 2-hydroxyethyl benzoate, lupenone, lupeol, saturated hydrocarbons, &beta; -sitosterol, stigmasterol.